2005
DOI: 10.1158/0008-5472.can-05-0824
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SFRP1 as a Candidate Mediator of Stromal-to-Epithelial Signaling in Prostate Cancer

Abstract: Genetic changes in epithelial cells initiate the development of prostatic adenocarcinomas. As nascent tumors grow and undergo progression, epithelial tumor cells are intimately associated with stromal cells. Stromal cells within the tumor microenvironment acquire new properties, including the capacity to promote phenotypic and genetic progression in adjacent epithelial cells. Affymetrix microarrays were used to identify 119 genes differentially expressed between normalderived and carcinoma-derived prostatic st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
136
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(143 citation statements)
references
References 41 publications
7
136
0
Order By: Relevance
“…Single cells obtained through out protocol were then cultured in RPMI 1640 with 5% FCS and 1 nM testosterone that allows continual growth of only the stromal populations. Each line was confirmed to display properties of CAFs in vitro including growth characteristics, immunomarkers, and RNA expression similar to previous reports [13,14]. In Supporting Information Figure S1, we show that SFRP-1 gene expression was significantly elevated in CAFs used in this study, compared to patientmatched normal prostatic fibroblasts (NPF)s; stromal lines were used between passages 3-6.…”
Section: Cell Lines and Stem Cell Enrichmentsupporting
confidence: 86%
See 1 more Smart Citation
“…Single cells obtained through out protocol were then cultured in RPMI 1640 with 5% FCS and 1 nM testosterone that allows continual growth of only the stromal populations. Each line was confirmed to display properties of CAFs in vitro including growth characteristics, immunomarkers, and RNA expression similar to previous reports [13,14]. In Supporting Information Figure S1, we show that SFRP-1 gene expression was significantly elevated in CAFs used in this study, compared to patientmatched normal prostatic fibroblasts (NPF)s; stromal lines were used between passages 3-6.…”
Section: Cell Lines and Stem Cell Enrichmentsupporting
confidence: 86%
“…While other investigators have studied the direct oncogenic activation of epithelial cells, we chose to apply two different stromal-based assays to indirectly test the effects on subpopulations of prostatic epithelia. First, CAFs derived from primary prostate cancer specimens show distinct genotypic and phenotypic differences compared to their nonmalignant matched controls and have been studied extensively in this BPH-1 cell assay [13,14,36,37]. The second model of hormonal carcinogenesis is based on administration of high doses of testosterone in combination with 17b-estradiol.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have noticed that the clone formation efficiency was lower in ADAR1-knockdown H9 cells than that in control cells (Supplementary information, Figure S1F). RNA-seq and RT-qPCR results further revealed that some key pro-apoptotic genes, such as S100A6 and BAX [31][32][33], were upregulated and the anti-apoptotic gene SFRP1 [34,35] was downregulated in ADAR1-knockdown H9 cells (Supplementary information, Figure S1G and Table S2), suggesting that ADAR1 deficiency can promote apoptosis of hESCs under certain stresses, such as enzymatic detachment. This is consistent with a previous report that cells cultured from ADAR1-deficient embryos exhibited increased apoptosis when a stress response was induced [24].…”
Section: Adar1 Knockdown Has Little Effect On Hesc Pluripotencymentioning
confidence: 98%
“…We consider the CAFs as part of these cancer microenvironment changes that occur in tissue lesions and serve as precursors for malignant disease. Several hypotheses have been presented for the origin of these altered cells, including standard connective tissue acute phase and stress response, 55,80,81 and fibroblast senescence, [82][83][84][85] reciprocal interactions with the cancer cells, 5,20,[86][87][88][89][90] fibroblast specific somatic mutations, [91][92][93][94][95] differentiation precursors and infiltrating mesenchymal stem cell. 96,97 …”
Section: The Mutational Model Of Cafsmentioning
confidence: 99%